Customer contributions to water sector planning and decision-making in England and Wales - Sayles, Rebecca (Cranfield University, 2015)
Mounting recognition of the socio-political context of the management of water resources has rendered the application of technocratic approaches in isolation insufficient in addressing future management challenges with participatory approaches increasingly promoted in response. Against this background, new regulatory mechanisms in the water sector in England and Wales promise an increased role for the views of customers in water utility planning and decision- making. Yet, existing scholarship on the institutionalisation of participative approaches in water utility planning and decision-making in England and Wales is sparse. This thesis contributes to an improved understanding of factors that hold potential to impact institutionalisation of participative approaches in this context by focusing on three specific aspects of effectiveness; motivational clarity, the influence of participative mechanism design, and the use and influence of water utility customer contributions in water sector planning and decision-making. This has been achieved through the deployment of participatory research in collaboration with the sponsoring organisation (a water utility operating in England and Wales) utilising group discussion and semi-structured interviews with domestic water customers and water utility practitioner respectively. Findings demonstrate that preference elicitation vehicles embedded within participatory mechanisms hold the potential to influence participants expressed preferences thus representing a key design consideration where multi- mechanism approaches are deployed in planning and decision-making contexts. Furthermore, useful design considerations for multi-attribute presentation in participatory mechanisms are presented. Findings also identify a dominance of instrumental and legalistic practitioner motivations for the use of participative approaches in water utility decision-making. Foremost, it identified the significance of the regulator in driving water utility practices for the management and influence of customer contributions in planning and decision- making, and more fundamentally illustrates the significant barrier posed by a legacy of technocratic practices for the institutionalisation of participatory approaches in water utilities.
Keywords: Public participation; water utilities; water resource management; participatory mechanisms; knowledge management